2015
DOI: 10.4049/jimmunol.1402736
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Increased B1 Cell Subset and Lupus Phenotypes in Mice and Humans Is Dependent on BLK Expression Levels

Abstract: Polymorphisms in the BLK gene have been associated with autoimmune diseases, including systemic lupus erythematosus (SLE), with risk correlating with reduced expression of BLK. How reduced expression of BLK causes autoimmunity is unknown. Using Blk+/+, Blk+/−, and Blk−/− mice, we show that aged female Blk+/− and Blk−/− mice produced higher anti-dsDNA IgG antibodies and developed immune complex-mediated glomerulonephritis, compared to Blk+/+ mice. Starting at young age, Blk+/− and Blk−/− mice accumulated increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…Blk –/– mice develop autoimmune disease, with anti‐dsDNA autoantibodies and immune complex–mediated glomerulonephritis, together with an increase in the proportion of B‐1 cells (a low‐affinity IgM‐producing subtype of B cells in mice) . Expansion of this subtype of B cells in other murine models of lupus is well documented and is thought to be important, particularly in driving nephritis . In a mechanism similar to that of the Lyp variant, this may contribute to autoimmunity by impairing central tolerance mechanisms.…”
Section: Variants Affecting B Cell Signaling Molecules Affect Both Pementioning
confidence: 99%
“…Blk –/– mice develop autoimmune disease, with anti‐dsDNA autoantibodies and immune complex–mediated glomerulonephritis, together with an increase in the proportion of B‐1 cells (a low‐affinity IgM‐producing subtype of B cells in mice) . Expansion of this subtype of B cells in other murine models of lupus is well documented and is thought to be important, particularly in driving nephritis . In a mechanism similar to that of the Lyp variant, this may contribute to autoimmunity by impairing central tolerance mechanisms.…”
Section: Variants Affecting B Cell Signaling Molecules Affect Both Pementioning
confidence: 99%
“…Remarkably, depletion of B1a cells by osmotic pressure ameliorates the development of type I diabetes [ 5 ], and reduces renal injury after kidney ischemia or reperfusion [ 9 ], indicating the involvement of B1a cells in disease progression. Early reports have found increased CD5 + B cells in patients with rheumatoid arthritis (RA) [ 10 , 11 ], Sjögren's syndrome [ 12 ] and systemic lupus erythematosus (SLE) [ 7 , 13 , 14 ]. Recent studies have characterized the human counterpart of murine B1 cells with the phenotype of CD20 + CD43 + CD27 + CD70 − present in the umbilical cord and adult peripheral blood [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Observations suggested that BLK was implicated in antibody production and possible formation of the TSHRAb in GD if BLK is dysregulated. Evidence showed that healthy subjects with the rs2736340 risk TT genotype have higher B1a‐like cells and higher circulating anti–double‐stranded (ds)DNA than those without the risk TT genotype . Moreover, Gourth et al demonstrated that rs13277113 and rs2736340 were associated with various autoantibodies and clinical subtypes in SS .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that healthy subjects with the rs2736340 risk TT genotype have higher B1a-like cells and higher circulating anti-double-stranded (ds)DNA than those without the risk TT genotype. 44 Moreover, Gourth et al demonstrated that rs13277113 and rs2736340 were associated with various autoantibodies and clinical subtypes in SS. 38 In this study, there were no correlations of the BLK SNPs, rs1377113 and rs2736340, with TSHRAb levels; thus, genetic variants only exerted a predominant role in F I G U R E 2 Anti-microsomal antibody (AmiA) titres at the baseline for different genotypes of rs13277113 (Panel A) and rs2736340 (Panel B), and the combined genotypes of rs3277113 and rs2736340 (Panel C) in autoimmune thyroid disease.…”
Section: Discussionmentioning
confidence: 99%